2015
DOI: 10.5089/9781498356305.001
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainty and Unemployment: The Effects of Aggregate and Sectoral Channels

Abstract: We study the role of uncertainty shocks in explaining unemployment dynamics, separating out the role of aggregate and sectoral channels. Using S&P500 data from the first quarter of 1957 to third quarter of 2014, we construct separate indices to measure aggregate and sectoral uncertainty and compare their effects on the unemployment rate in a standard macroeconomic vector autoregressive (VAR) model. We find that aggregate uncertainty leads to an immediate increase in unemployment, with the impact dissipating wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Part of this literature, which considers the implications of uncertainty on labor market is more scarce. Empirically work (see Caggiano and Groshenny (2014), Choi and Loungani (2015), Leduc and Liu (2016)) shows that a rise in aggregate uncertainty increases unemployment. Theoretical literature has shown that labor market frictions amplify the effects of uncertainty similar to investment irreversibility through the real option-value channel in the labor market.…”
Section: Figure 1 Macro Uncertainty and Skill Premiummentioning
confidence: 99%
See 2 more Smart Citations
“…Part of this literature, which considers the implications of uncertainty on labor market is more scarce. Empirically work (see Caggiano and Groshenny (2014), Choi and Loungani (2015), Leduc and Liu (2016)) shows that a rise in aggregate uncertainty increases unemployment. Theoretical literature has shown that labor market frictions amplify the effects of uncertainty similar to investment irreversibility through the real option-value channel in the labor market.…”
Section: Figure 1 Macro Uncertainty and Skill Premiummentioning
confidence: 99%
“…Caggiano and Groshenny (2014) andChoi and Loungani (2015) are examples of previous studies that found the importance of this channel.©International Monetary Fund. Not for Redistribution…”
mentioning
confidence: 93%
See 1 more Smart Citation